Book as the point of the conflict of cultures: the mission of St. Adalbert in Prussia - Ališauskas, Vytautas (Literatūra, 2015)
The first Prussians’ encounter with Christianity ended in the martyrdom of the missionary St. Adalbert; it took place on the 23rd of April, 997. What provoked his martyrdom is far from clear to this day. According to some hypotheses, the Prussians were provoked by St. Adalbert’s unfamiliar pontifical vestments that he put on to celebrate Mass, or simply by his unacceptable appearance. The present paper draws attention to the beginning of the conflict with the Prussians. Its cause is St. Adalbert’s unusual behaviour – reading prayers from a book. This could have been perceived as a way of communicating with the supernatural world which threatened the community, as a magic charm. It is important to note the day when St. Adalbert was martyred. According to the Christian calendar this is St. George’s day. In many countries of Central and Eastern Europe this is the day when working the fields symbolically begins. Later sources attest that the pagan Prussian festival of the rebirth of nature, the celebration of spring which was supposed to guarantee future harvest, coincided with this day. Christian missionary with his rituals, externally based on the reading of liturgical books, may have created a perception that his activities would harm future fertility of the earth and animals.